Organic Dyes Containing Coplanar Dihexyl-Substituted Dithienosilole Groups for Efficient Dye-Sensitised Solar Cells - Ciaran Lyons; Neelima Rathi; Pratibha Dev; Owen Byrne; Praveen K. Surolia; Pathik Maji; J. M. D. MacElroy; Aswani Yella; Michael Grätzel; Edmond Magner; Niall J. English; K. Ravindranathan Thampi (International Journal of Photoenergy, 2017)
A chromophore containing a coplanar dihexyl-substituted dithienosilole (CL1) synthesised for use in dye-sensitised solar cells displayed an energy conversion efficiency of 6.90% under AM 1.5 sunlight irradiation. The new sensitiser showed a similar fill factor and open-circuit voltage when compared with N719. Impedance measurements showed that, in the dark, the charge-transfer resistance of a cell using CL1 in the intermediate-frequency region was higher compared to N719 (69.8 versus 41.3 Ω). Under illumination at AM 1.5G-simulated conditions, the charge-transfer resistances were comparable, indicative of similar recombination rates by the oxidised form of the redox couple. The dye showed instability in ethanol solution, but excellent stability when attached to TiO2. Classical molecular dynamics indicated that interactions between ethanol and the dye are likely to reduce the stability of CL1 in solution form. Time-dependent density functional theory studies were performed to ascertain the absorption spectrum of the dye and assess the contribution of various transitions to optical excitation, which showed good agreement with experimental results.